Iceland : Technical Assistance Report-Optimal Reform and Distributional Analysis of the Personal Income Tax. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses key findings and recommendations of the Technical Assistance Report on Optimal Reform and Distributional Analysis of the Personal Income Tax (PIT). With regard to reforming the PIT schedule, it recommends that the basic credit be increased and made fully refundable to all taxpayers age 18 and older. To avoid paying this benefit to young singles, such as students, who generally have other means of support, it could be conditioned on a certain level of labor earnings. This credit should be rapidly phased out as labor income rises, and the initial PIT rate should be significantly reduced. The current top PIT rate does not need reform, although the threshold for that rate should ideally be raised.